The effect of embryo catheter loading technique on pregnancy rate. Issue 2 (24th May 2022) - Matitashvili, Tamar; Sadek, Seifeldin; Celia, Gerard
Abstract : Lay summary: Embryo transfer is the most emotional part for patients during in vitro fertilization treatment. Over the last decade, the embryo transfer procedure has undergone numerous changes in the guidelines in order to increase pregnancy rates. One such procedure is the loading of the embryo into the catheter, a thin tube that helps us transfer embryo into the uterine cavity. Very few research studies looked closely at embryo-loading technique per se. Furthermore, different infertility laboratories use various techniques to load embryo. The aim of our study was to compare the two most popular embryo-loading techniques. In 249 women, we transferred embryo aspirated into the catheter with small droplets of air, and in the group of 244 patients, we filled catheter only with fluid. Our main outcome measured was the clinical pregnancy rate. Based on our results, we did not find that embryo-loading technique affected patient's chances of achieving pregnancy.